Cytomorphometric Analysis of Exfoliated Buccal Mucosal Cells in Diabetic Patients - Jahan, Mahmuda; Rahman, Zillur; Sultana, Nasrin; Begum, Mahmuda; Ahamed, M Shahab Uddin; Ahmed, Syed (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Diabetes mellitus is a common metabolic disease that causeschronic hyperglycemia and disturbance in carbohydrate, lipid and proteinmetabolism. It causes various changes in the cells of the oral mucosa, which canbe determined by exfoliative cytology. The aim of this study was to study theCytomorphometric alterations of exfoliated buccal mucosal cells in diabeticpatients and to establish an additional diagnostic tool in diabetic patients inChattogram area. Materials and methods: It was a cross-sectional comparative study carried outin the Department of Pathology, Chattogram Medical College, Chattogram. Oralsmears were obtained from 88 diabetic patients and 88 healthy individuals. Thesmears were stained with Papanicolaou solution. The cell diameter and nucleardiameter of 50 clearly defined cells were measured by multi-head microscope(OLYMPUS B51X). The cytoplasmic area and nucleus-cytoplasmic ratio werethen calculated. SPSS software (version 17) was used for statistical analysis ofthe study. Results: In the result, mean Cell Diameter (CD), Nuclear Diameter (ND),cytoplasmic diameter (CyD) and N/C ratio of diabetic patients and healthy werefound to be 250.29 ± 29.02 μm, 54.48 ± 4.03 μm, 195.81 ± 27.97 μm, 0.283 ±0.04 and 287.15 ± 25.23 μm, 47.41 ± 2.52 μm, 239.74 ± 24.45 μm, 0.199 ± 0.02.A statistically significant increase in ND & N/C ratio and decrease in CD &CyDwere observed in diabetic patients compared to control. In addition, it wasfound that age, sex, blood sugar level, duration and treatment history ofdiabetes do not affect the morphometric changes significantly. Conclusions: Result of this study suggests that diabetes produces definitemorphometric changes in the exfoliated buccal mucosal cells. Exfoliativecytology can be useful as an additional tool to aid in diagnosis of diabetesmellitus. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 3-7